AN INSIGHT INTO BUSINESS ADMINISTRATION GRADUATES’ ENGLISH ORAL COMMUNICATION COMPETENCIES FROM WORKPLACE PERSPECTIVES - Minh Tram, Nguyen Thi (VNU Journal of Foreign Studies; Vol 36 No 1, 2020)
The issue of discrepancies between university English business administration curriculum and English oral communication competence requirements in the workplace has been increasingly alarming since Vietnam accessed into more and more international business organizations especially ASEAN Economic Community. In the present study, qualitative data were collected in semi-structured interviews with stakeholders in real workplace, consisting of 15 employers at executive and managerial level and 8 business administration graduates from four universities to explore this mismatch. The results showed that most of the employers and graduates were slightly dissatisfied or dissatisfied with business administration graduates’ English oral communication competencies in workplace right after their graduation. Specifically, most of the business administration graduates lacked good pronunciation, skills and appropriate attitudes rather than knowledge in dealing with English oral communication tasks. Importantly, much of the dissatisfaction of both employers and graduates came from the discrepancies between the university preparation and workplace requirements. Thus, creating long-term collaborative partnerships among and between academic institutes and potential employers and designing a competency-based course are essential in preparing business administration undergraduates efficiently for the increasingly demanding workplace regarding English oral communication competencies.